Quality Care Within The Hospital Management - Nadia, Bouzgarrou; Lamia, Bouzgarrou; Benchekroun, Tahar Hakim (Advances in Social Sciences Research Journal, 2014)
Within the health sector, the concept of quality is becoming increasingly important and being paid more attention by officials. Therefore, the quality standard was introduced in hospital practices thus requiring the establishment a Quality Management System (QMS) which provides quality as the responsibility of all the hospital staff (administrative, medical and paramedical) so as to be up to offer a service that responds to the concerns and needs of patients. The Quality in hospitals corresponds to the balance between hospital services and the needs and expectations of the patients according to medical knowledge and texts rigors. It incorporates an intrinsic component of safety and reliability of health care. All these specificities raised on quality imply that in the health sector, a development and implementation tooling must be naturally established. As a matter of fact, both standardization and certification are among the main tools of quality.